Increased Levels of Plasma Extracellular Heat-Shock Proteins 60 and 70 kDa Characterized Early-Onset Neonatal Sepsis - Arturo Alejandro Canul-Euan; Gibran Zúñiga-González; Janelly Estefania Palacios-Luna; Rolando Maida-Claros; Néstor Fabián Díaz; Patricia Saltigeral-Tigeral; Perla Karina García-May; Oscar Díaz-Ruiz; Héctor Flores-Herrera (Frontiers Media S.A., 2021)
Background: Extracellular heat-shock proteins (eHsp) are highly conserved molecules that play an important role in inflammatory diseases and have been quantified in plasma from patients with infectious diseases, including sepsis. There is a constant search for dependable biochemical markers that, in combination with conventional methods, could deliver a prompt and reliable diagnosis of early-onset neonatal sepsis.Objective: We sought to assess the level of eHsp-27, eHsp-60, eHsp-70, and tumor necrosis factor-alpha (TNFα) in plasma of healthy neonates at term and infants with early-onset neonatal sepsis.Methods: This study included 34 newborns that were classified as healthy neonates at term (blood samples from the umbilical cord, n = 23) or infants with early-onset neonatal sepsis (blood samples obtained from umbilical artery by standard sterile procedures before starting a systemic antibiotic intervention, n = 11). All blood samples were centrifuged, and the plasma recovered to determine eHsp-27, eHsp-60, eHsp-70, and TNFα levels by ELISA.Results: Our results indicate that the level of eHsp-27 in healthy neonates at term was 0.045 ± 0.024 pg/ml. This value decreased 2.5-fold in infants with early-onset neonate sepsis (0.019 ± 0.006 pg/ml, p = 0.004). In contrast, the levels of eHsp-60 and eHsp-70 in healthy neonates at term were 13.69 ± 5.3 and 4.03 ± 2.6 pg/ml, respectively. These protein levels increased significantly 1.8- and 1.9-fold in the plasma of infants with early-onset neonatal sepsis (p ≤ 0.001). The level of TNFα in healthy neonates at term was 2.94 ± 0.46 pg/ml, with a 3.0-fold increase in infants with early-onset neonatal sepsis (8.96 ± 0.72 pm/ml, p ≤ 0.001). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of eHsp compared with that of C-reactive protein were 73.3, 60.0, 47.8, and 33.3%, respectively.Conclusion: This study demonstrated a consistent increase of eHsp-60 and eHsp-70 in the plasma of infants diagnosed with early-onset neonatal sepsis. These proteins showed higher sensitivity and specificity than C-reactive protein and blood culture test.